2019
DOI: 10.26508/lsa.201900459
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein-independent IRE1 activation contributes to multifaceted developmental processes in Arabidopsis

Abstract: The Arabidopsis unfolded protein response transducer IRE1 contributes to male gametophyte development using an alternative activation mechanism bypassing the unfolded protein-sensing domain.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…A. thaliana has three IRE1 genes, two full length genes, AtIRE1a and -b, discovered by Koizumi et al (2001), and a shorter version called AtIRE1c (Figure 4). Arabidopsis lyrata has four IRE1 genes, AlIRE1a, -b, -c and c-like (Mishiba et al, 2019). Surprisingly, there are three ZmIRE1 genes in maize (Zea mays B73)two full-length genes, which cannot be classified as either IRE1a or -b-like and a shorter one, which by virtue of its size suggests that it is IRE1c-like.…”
Section: Are Two Ire1s Better Than One?mentioning
confidence: 99%
See 1 more Smart Citation
“…A. thaliana has three IRE1 genes, two full length genes, AtIRE1a and -b, discovered by Koizumi et al (2001), and a shorter version called AtIRE1c (Figure 4). Arabidopsis lyrata has four IRE1 genes, AlIRE1a, -b, -c and c-like (Mishiba et al, 2019). Surprisingly, there are three ZmIRE1 genes in maize (Zea mays B73)two full-length genes, which cannot be classified as either IRE1a or -b-like and a shorter one, which by virtue of its size suggests that it is IRE1c-like.…”
Section: Are Two Ire1s Better Than One?mentioning
confidence: 99%
“…IRE1c is largely limited to the Brassicas, is a smaller form that lacks the N-terminal lumenal or sensory domain and is expressed primarily in flowers (Winter et al, 2007;Figure 4). Reporter constructs involving the IRE1c promoter demonstrated that the gene is expressed in the anther and embryo (Mishiba et al, 2019) Moreno et al (2012) [Colour figure can be viewed at wileyonlinelibrary.com] for a long time, because single knockout mutations in IRE1c had no demonstrable phenotype. However, a role of IRE1c came to light when two groups created a triple ire1a/b/c mutant and reported that it was lethal, and when a heterozygous IRE1c mutation was created in conjunction with ire1a/ire1b (ire1a/ire1b/ire1c/+) it was found to be defective in male gametogenesis (Mishiba et al, 2019;Pu et al, 2019).…”
Section: The Weirdness Of Ire1cmentioning
confidence: 99%
“…While this manuscript was under revision, complementary work on the characterization of IRE1C was published (Mishiba et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, an EMS-based genetic screen identified a plastidial stearoyl-acyl carrier protein desaturase, responsible for the conversion of stearic acid (18:0) into oleic acid (18:1), as an upstream regulator of UPR [ 246 ]. Thirdly, glycerol application to seedlings, that was shown to augment steady-state levels of saturated lipids, was able to induce RIDD, but bZIP60 splicing, in ire1 double mutant background engineered for expressing a luminal domain-deleted IRE1B protein [ 247 ]. Therefore, it is likely that lipo-toxic ER stress could actuate a protective RIDD response in Arabidopsis.…”
Section: Autophagy Rewires Cellular Activities To Mediate Plant Adaptation To Stress: the Complex Relationship Between Autophagy And Lipimentioning
confidence: 99%